Analisis Yuridis Terhadap Proses Penetapan Status Tersangka Tindak Pidana Korupsi - Sahidu, Fikhan; Harun, Rina Rohayu; Erwin, Yulias (Universitas Muhammadiyah Yogyakarta, 2024)
Corruption is categorized as an extraordinary crime because it has an extraordinary impact so that its handling must also be carried out in extraordinary ways. The law has given investigators the authority to enforce the law such as determining suspects, detention, and searches. The other side shows how this authority is often misused such as errors in determining suspects, victims of mistaken arrest, law enforcement officials who are caught in corruption and others. This fact makes the professionalism of investigators questionable so that to overcome abuse and arbitrary actions that may occur, a pretrial institution is formed. The problems underlying the pretrial application in this paper refer to the allegation that investigators did not notify or submit a Letter of Commencement of Investigation (SPDP), the determination of suspects had no initial evidence and the calculation of findings of state losses was not based on the results of BPK calculations. The research method used is normative legal research which is sourced from secondary data and analyzed narratively with qualitative descriptive. Based on the research results, it is known that the Praya District Court granted the pretrial motion and determined that the suspect determination letter in the name of the applicant with the number: print-68/n.2.11/fd.1/06/2023 dated June 8, 2023 was invalid and had no binding legal force